2000
DOI: 10.1123/ijsnem.10.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Eating Pattern and Nutritional Status of International Elite Flatwater Paddlers

Abstract: The aim of this study is to accurately describe the eating pattern and nutritional status of international elite flatwater paddlers during 1 week of a high volume training camp. Ten male and 5 female international elite flatwater paddlers were recruited to take part in this study. These athletes were all members of the Spanish National Team. To assess the intake of energy, macronutrients, and micronutrients, we used the weighed food intake method carried out by an observer. Biochemical and hematological profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…Muy inferior a los valores ideales fue el consumo de frutos secos. Estos resultados difieren parcialmente de los encontrados en piragüistas de elite (García-Rovés et al, 2000) y en deportistas olímpicos (Vega, 1994), ya que -en general-estos tenían unos hábitos alimentarios más saludables. Las divergencias entre los diferentes estudios podrían deberse a la heterogeneidad de las poblaciones estudiadas en cuanto a edad y nivel competitivo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Muy inferior a los valores ideales fue el consumo de frutos secos. Estos resultados difieren parcialmente de los encontrados en piragüistas de elite (García-Rovés et al, 2000) y en deportistas olímpicos (Vega, 1994), ya que -en general-estos tenían unos hábitos alimentarios más saludables. Las divergencias entre los diferentes estudios podrían deberse a la heterogeneidad de las poblaciones estudiadas en cuanto a edad y nivel competitivo.…”
Section: Discussionunclassified
“…De hecho, en un grupo de élite formado por mujeres kayakistas adolescentes también se encontró que las participantes no tenían unos hábitos alimentarios totalmente saludables (Alacid et al, 2014) Por tanto, de acuerdo con lo encontrado en deportistas de diferentes modalidades y edades (Ocaña et al, 2009;García-Rovés et al, 2000), la mayoría de las deportistas de la presente muestra deben mejorar su dieta, si bien sus hábitos alimentarios son mejores que los de la población sedentaria o los de individuos de otras modalidades deportivas. El hecho de que los piragüistas de la presente investigación no presenten una dieta del todo equilibrada es especialmente importante si se tiene en cuenta que este deporte requiere un gran volumen de entrenamiento, lo que, según trabajos realizados en deportes de características fisiológicas similares, podría desembocar en déficit de energía y algunos nutrientes (Ousley-Pahnke, Black y Gretebeck, 2001), lo cual disminuye su rendimiento y aumenta las probabilidades de sufrir algún tipo de lesión (García-Rovés et al, 2000).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Furthermore, when protein balance is challenged due to suboptimal intake, it is possible the body will adapt with an increased preference for proteinrich foods in order to restore balance without increasing energy intake [82]. Given that many athletes fall short on the appropriate distribution of protein across the day [83,84], and the protein needs of athletes are higher [12], the protein leverage concept may play an even greater role amongst individuals with active lifestyles.…”
Section: Macronutrient Balancementioning
confidence: 99%
“…It has frequently been reported that the spontaneous nutritional intake of athletes is related to the physiological and metabolic demands of their sport [96,97,98,99]. Many authors have described position-related differences in the performance capabilities and physiological and anthropometric characteristics of soccer players.…”
Section: Correlates Of the Eating Practice And Nutritional Intake mentioning
confidence: 99%